Clinical and imaging features of children with autoimmune encephalitis and MOG antibodies. Issue 4 (July 2020) - Wegener-Panzer, Andreas; Cleaveland, Robert; Wendel, Eva-Maria; Baumann, Matthias; Bertolini, Annikki; Häusler, Martin; Knierim, Ellen; Reiter-Fink, Edith; Breu, Markus; Sönmez, Özcan; Della Marina, Adela; Peters, Renate; et al.
Abstract : Objective: To describe the presentations, radiologic features, and outcomes of children with autoimmune encephalitis associated with myelin oligodendrocyte glycoprotein antibodies (MOG abs). Methods: Identification of children fulfilling the diagnostic criteria for possible autoimmune encephalitis (AE) and testing positive for serum MOG abs. Chart review and comprehensive analysis of serum MOG abs using live cell assays and rat brain immunohistochemistry. Results: Ten children (4 girls, 6 boys) with AE and serum MOG abs were identified. The median age at onset was 8.0 years (range: 4–16 years). Children presented with a combination of encephalopathy (10/10), headache (7/10), focal neurologic signs (7/10), or seizures (6/10). CSF pleocytosis was common (9/10, median 80 white cell count/μL, range: 21–256). Imaging showed cortical and deep gray matter involvement in all in addition to juxtacortical signal alterations in 6/10 children. No involvement of other white matter structures or contrast enhancement was noted. MOG abs were detected in all children (median titer 1:640; range: 1:320–1:10, 540). Nine children had a favorable outcome at discharge (modified Rankin scale of < 2). Five of 10 children had up to 3 additional demyelinating relapses associated with persisting MOG abs. One child had NMDA receptor (NMDAR) abs at initial presentation. A second child had a third demyelinating episode with MOG abs with overlapping NMDAR encephalitis. Discussion: AE associated with serum MOG abs represents a distinct form of autoantibody-mediated encephalitis in children. We therefore recommend including MOG abs testing in the workup of children with suspected AE.